UJI EFEKTIVITAS BEBERAPA EKSTRAK TANAMAN TERHADAP PERTUMBUHAN CENDAWAN PENYEBAB ANTRAKNOSA (Colletotrichum sp.) PADA BUAH PEPAYA: Effectiveness Test Of Several Plant Extracts On The Growth Of Fungi Causing Anthrachnose (Colletotrichum sp.) On Papaya Fruit - rahmaniar; Yulis sayang; Suriani (Fakultas Pertanian Universitas Islam Makassar, 2025)
The aim of this study was to evaluate and determine the effectiveness of various plnat extracts in inhibiting the growth of Colletotrichum sp. in vitro. The research was conducted at the Plant Protection Laboratory, Faculty of Agriculture, Islamic University of Makassar. Symptomatic papaya fruits infected by Colletotrichum sp. were collected from Daya Market, Makassar City. The study employed a completely randomized design consisting of a control and four plant extract treatments (betel leaf, papaya leaf, ginger rhizome, and shallot peel), each at a 15% concentration. Observations were carried out by measuring the growth diameter and calculating the inhibition percentage of Colletotrichum sp. colonies. The results showed that all plant extracts were able to inhibit the growth of Colletotrichum sp. in-vitro. Betel leaf extract was the most effective in inhibiting the growth of Colletotrichum sp. with the highest inhibition of 45.22%.